Identification of pollen-expressed pectin methylesterase inhibitors in Arabidopsis - Wolf, Sebastian; Grsic-Rausch, Slobodanka; Rausch, Thomas; Greiner, Steffen (FEBS letters, 2003)
Pectin methylesterases (PMEs) play an essential role during plant development by affecting the mechanical properties of the plant cell wall. Previous work indicated that plant PMEs may be subject to post-translational regulation. Here, we report the analysis of two proteinaceous inhibitors of PME in Arabidopsis thaliana (AtPMEI1 and 2). The functional analysis of recombinant AtPMEI1 and 2 proteins revealed that both proteins are able to inhibit PME activity from flowers and siliques. Quantitative RT-PCR analysis indicated that expression of AtPMEI1 and 2 mRNAs is tightly regulated during plant development with highest mRNA levels in flowers. Promotor::GUS fusions demonstrated that expression is mostly restricted to pollen.